2017
DOI: 10.1097/md.0000000000006568
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of anterior cruciate ligament reconstruction using LARS artificial graft with an at least 7-year follow-up

Abstract: The aim of our study was to assess the medium-term clinical outcomes of anterior cruciate ligament (ACL) reconstruction using the Ligament Advanced Reinforcement System (LARS) artificial ligament.A total of 168 patients who underwent arthroscopic ACL reconstruction with the LARS artificial ligament in our department were enrolled in our research. Only 125 met the inclusion/exclusion criteria, and 91 could ultimately be contacted to participate in our research. The mean follow-up was 92 ± 19 months. Physical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 19 publications
1
34
0
3
Order By: Relevance
“…As a result of suboptimal biological properties on these devices, rates of clinical failure or complications reported in various clinical studies for the more recent Leeds–Keio (LK) and LARS constructs range from 15% to 28% for LK and from 2.3% to 0% (mean ± standard deviation (SD) = 20 ± 15.2% across the selected refs …”
Section: Straight Synthetic Dry Fibrous Materials For T/l Repair—learmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of suboptimal biological properties on these devices, rates of clinical failure or complications reported in various clinical studies for the more recent Leeds–Keio (LK) and LARS constructs range from 15% to 28% for LK and from 2.3% to 0% (mean ± standard deviation (SD) = 20 ± 15.2% across the selected refs …”
Section: Straight Synthetic Dry Fibrous Materials For T/l Repair—learmentioning
confidence: 99%
“…for LARS. There is no current US Food and Drug Administration approved synthetic T/L for clinical use, though both LK and LARS have been in recent clinical circulation in Europe, Asia, and Australia . Synthetic T/L implant failures often present symptoms such as joint instability, which can be confirmed with either intra‐arthroscopic or noninvasive imaging—though contrast with surrounding tissue is often poor for such methods—and pain which often arises from the chronic inflammatory activity associated with extensive foreign body reactions characterized by the presence of numerous foreign body giant cells and can be confirmed histologically ( Figure ).…”
Section: Straight Synthetic Dry Fibrous Materials For T/l Repair—learmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogenic grafts are also frequently used, but they carry a potential risk of immune rejection, infection, and delayed healing. Synthetic osteochondral grafts have been used for the treatment of osteochondral lesions (Pearce et al, 2012), and they provide a viable alternative option to both autologous and allogenic grafts but are still under evaluation for their large-scale clinical applications (Jia et al, 2017). Another significantly advanced approach for the healing of damaged articular cartilage is autologous chondrocyte implantation (ACI), which involves arthroscopic removal of a small piece of articular cartilage from the patient's knee for self-repair.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Ligament Advanced Reinforcement System (LARS) ligament (Surgical Implants and Devices, Arc-sur-Tille, France), which is made from polyethylene terephthalate (PET), is one of the choices for grafting in ACL injury 5 . Several clinical studies have shown that the LARS ligament possesses several potential postoperative benefits, including the early return to unrestricted sports and strenuous activities, and avoidance of complications caused by using the autografts or allografts, which indicates that it is a good choice for use in ACL reconstruction [6][7][8][9] . However, some failure cases have been reported when this artificial ligament is used for reconstructing ACL [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%